Laparoskopska histerektomija - Kobal, Borut (Endoskopska revija, 2005)
Laparoscopic hysterectomy represents a safe alternative to abdominal hysterectomy in the operative treatment of benign and some selected malignant diseases of the uterus. The author presents the indications for the procedure,and summarizes his own and other authors' experience with the new technigue. The learning curve is between 20 to 30 laparoscopic hysterectomies.The technigue enables the surgeon to make use of all advantagesoffered by the minimally invasive surgery, particularly in terms of lesser perioperative morbidity rate and shorter postoperative recovery period.
Keywords: Histerektomija; Hysterectomy; Histerektomija vaginalna; Surgery, Laparoscopic; ginekologija; Hysterectomy, Vaginal; laparoskopska kirurgija